2021
DOI: 10.3991/ijet.v16i11.19421
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Digital Technology Integration on Students’ Academic Performance through Project-Based Learning in an E-learning Environment

Abstract: This study aimed to develop a model to examine how digital technology integration contributes to the enhancement of students’ academic performance through project-based learning (PBL) amongst undergraduates in higher education. In this study, the technology acceptance model (TAM) was used as the basic model to explore the digital technology environment in terms of the perceived usefulness, perceived ease of use and attitude towards integrating digital technology and the influence of these factors on undergradu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
18
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 34 publications
(23 citation statements)
references
References 44 publications
(71 reference statements)
3
18
0
2
Order By: Relevance
“…The results also indicate that the pre-service teacher participants' attitudes were positively determined by perceived usefulness and perceived ease of use. These findings are consistent with previous research, i.e., [45] [46]. According to [36], when using a particular technology, the level of an individual's confidence plays a significant role in their attitude toward the adoption of such technology.…”
Section: Discussionsupporting
confidence: 92%
“…The results also indicate that the pre-service teacher participants' attitudes were positively determined by perceived usefulness and perceived ease of use. These findings are consistent with previous research, i.e., [45] [46]. According to [36], when using a particular technology, the level of an individual's confidence plays a significant role in their attitude toward the adoption of such technology.…”
Section: Discussionsupporting
confidence: 92%
“…It is a known fact that academic success is affected by the characteristics of students, their motivation, or situations such as anxiety (Hauze & Marshall, 2020, Park et al, 2022. In the use of e-learning technologies, many factors that can affect students' attitudes such as the design of the course or the methods and techniques used in the teaching of the course, the adequacy of the interaction between the student and the educator, and the quality of the teaching have been stated to play an important role in the academic success of the students (Al-Abdullatif & Gameil, 2021;Singh et al, 2021;Li et al, 2021,). The results of a qualitative study showed that concerns of NSs' toward e-learning differ according to the years of education, and the concern and worry of the students in the first year of their education are mostly associated with the changes in the learning strategies to be used and the fears of failure that this may lead to (Suliman et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…This model advises that practical activities should be carried out in groups in a collaborative way so that there can be an exchange of knowledge and experience between students, and it is possible to replicate the situations that may occur in industry. These practices might arise from employing different methodologies, and include: practical projects [22], PBL [33], [34], serious games [35] or programming dojos [10]. It is advisable that a professor or other professional should supervise these practical activities so that they can coach and mentor the groups, sort out any technical problems, assist in the way the practices are carried out and act as a mediator if any possible conflicts arise in the groups.…”
Section: Phase Iv: Practical and Collaborative Activitiesmentioning
confidence: 99%